The Influence of International Legal Frameworks on Peacebuilding in the Bangsamoro Region: An Assessment of Acceptance, Perception, and Application - Fazlurrashed S. Paslangan; Laniel Ryan P. Untong (RIRAI Publisher, 2026)
This study explores how International Humanitarian Law (IHL), International Human Rights Law (IHRL), and Islamic Law intertwine to shape peacebuilding in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). Drawing on deep-dive interviews with eight influential leaders from state security forces, non-state armed groups, and regional governance bodies, the research uncovers a complex legal landscape where global standards meet deeply rooted faith. The findings reveal that while international frameworks are respected for their operational utility in limiting conflict and building trust, Islamic Law remains the heartbeat of the region’s identity and the primary lens through which justice is understood. This acceptance, however, exists in a delicate balance—it is